Assessing neuromotor readiness for learning : the INPP developmental screening test and school intervention programme - Goddard, Sally, 1957-; Wiley InterScience (Online service) (Malden, MA : Wiley-Blackwell, 2012)
"Assessing Neuromotor Readiness for Learning is a substantially revised and expanded edition of a long established INPP training manual that has been consistently proven in practice. The package includes tests for children, a developmental movement programme, and online access to INPP video training materials. Based on the proven INPP model for neuromotor development screening and intervention, which is unique in having been rigorously evaluated in research and practice Expands and revises an INPP manual which has previously only been available to training customers, and which is a foundation stone of the overall INPP approach Places emphasis on children's physical development and how neuro-motor skills provide the foundations for learning success. The package includes batteries of tests for younger and older children, a developmental movement programme, and online access to INPP video training materials"--Provided by publisher.
"Assessing Neuromotor Readiness for Learning is based on an established training manual which has been in use as part of INPP's popular training courses, and is a foundation stone of the overall INPP approach"--Provided by publisher.
Front Matter -- Introduction -- Developmental Screening Tests for Use with Children Aged 4b6(B7 Years -- Developmental Screening Tests for Use with Children from 7 Years of Age -- The INPP Developmental Movement Programme -- Resources.s
Includes bibliographical references and index.
Print version record.
Keywords: Learning disabled children -- Education; Learning disabilities -- Physiological aspects; Movement disorders in children -- Diagnosis; Movement disorders in children -- Treatment; Motor ability -- Testing; PSYCHOLOGY -- Developmental -- General; Electronic books